Norlevo and conscience objection. - Di Pietro, M.L.; Casini, M.; Fiori, A.; Minacori, R.; Romano, L.; Bompiani, A. (Medicina e Morale, 2003)
The authorisation of the marketing, in Italy, of Norlevo (levonorgestrel) as emergency contraception method (Decree AIC/UAC n. 510/2000 of 26.9.2000) has risen an intense debate on the physician that doesn't want to prescribe drugs, that can hinder the pursuance of the development of the conceived, for deontological and ethical reasons. Besides, it is argued if this decision can fall within the circumstance foreseen by the art. 9 of the Italian Act 194/78 on voluntary abortion about conscience objection. To give an answer to this question, it is necessary - first of all - to study the mechanism of action of the levonorgestrel: only if there is the possibility of an abortive effect, it would have been possible to appeal to the aforesaid act. The specific juridical reflection is analysed, since the authors conclude that, close to the contraceptive effect, there is also present an effect on postfertilization. In the light of the Italian Law and of the decisions of the Italian Constitutional Court, the physician refusal to prescribe the Norlevo fall within the forecasts of the art. 9 of the Act 194/78, but also if this would not be recognized, it is always justifiable, in front of the good of human life, a clause of conscience on the grounds of the physician's right to act according to own beliefs.